An Analysis of Community Perceptions of Golkar Party Performance in the Development of Mojotrisno Village, Mojoagung, Jombang (2019–2024) - Mochdar Soleman (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2026)
This study aims to analyze community perceptions of the performance of the Golkar Party in Mojotrisno Village, Mojoagung District, Jombang Regency, as well as the factors influencing these perceptions. The research employs a qualitative descriptive method, with data collected through observation, interviews, and documentation. The findings indicate that community perceptions of the Golkar Party tend to be unfavorable, as reflected in the limited public understanding of the party’s roles, functions, and programs. The community tends to recognize the party more in symbolic and historical terms rather than in substantive aspects. This condition is influenced by limited access to information, low levels of political interaction, and the lack of party outreach and presence at the local level. In addition, low public trust, political competition, and the dynamics of digitalization further reinforce these perceptions. The findings reveal a gap in political communication between the party and the community, which contributes to low levels of political participation. Therefore, strengthening communication strategies, enhancing the party’s presence at the local level, and adopting more adaptive approaches are necessary to improve public understanding and engagement in political life